The risk of bias of non-randomized observational studies in deep inferior epigastric perforator flap breast reconstruction: A systematic review using ROBINS-I. Issue 11 (November 2022) - Yuan, Morgan; Wu, Jeremy; Lee, James; Cao, Daniel; Huynh, Minh NQ; Gallo, Lucas; O' Neill, Anne C; Hofer, Stefan O.P.
Summary: Introduction: The deep inferior epigastric perforator (DIEP) flap is regarded as the gold standard for autologous breast reconstruction. However, due to difficulty designing and conducting randomized controlled trials in surgical interventions, the majority of literature on DIEP flap breast reconstructions are observational studies. As such, it is pivotal that these studies are performed with high internal validity. Methods: A literature search was performed using MEDLINE, Embase, and CENTRAL from January 1, 2015 to October 23, 2021. Studies identified as observational studies about DIEP breast reconstruction and published in a journal with a Web of Science impact factor above 1.0 were included. Screening and risk of bias (RoB) assessment using the ROBINS-I tool were performed independently and in duplicate by two authors. Results: From 12, 371 studies, 66 observational studies were included. The majority were found at RoB, with 11 at moderate, 26 at serious, and 6 at critical RoB. Only two studies had low RoB. The bias most commonly arose due to Domain 1 (confounding variables), Domain 3 (classification of interventions), and Domain 6 (measurement of outcomes). Conclusions: In this review, we demonstrate the high RoB of observational studies evaluating DIEP breast reconstruction, which may jeopardize the validity of findings. We recommend that authors consult the ROBINS-I tool not only when assessing observational studies for systematic reviews but also when designing or conducting these studies. In our study, we present additional considerations for each domain to provide researchers with guidance on assessing and conducting surgical observational studies.